Fracture Behavior of Rock with Initial Damage: Theoretical, Experimental, and Numerical Investigations - Hui Zhang; Panpan Guo; Yixian Wang; Yanlin Zhao; Hang Lin; Yan Liu; Yahui Shao (Geofluids)
Geomaterials such as rock mass often have initial damage under the influence of long-term geological action and hydration corrosion environment. The initial damage affects the integrity and stability of the rock mass, resulting in a difference in the mechanical properties of jointed rock mass and intact one. Therefore, the study of the fracture and failure characteristics of the jointed rock mass is of great significance. Most of the previous researches into the fracture behavior of rock with initial damage are based on model testing, theoretical analysis, and numerical simulation of rock mass with preexisting flaws. This review concentrates on the theoretical, experimental, and numerical efforts that have been devoted to the fracture characteristics of rock or rock-like specimens with preexisting flaws under compression. Some suggestions on the future research work in this field are also given.